2013
DOI: 10.1037/a0031476
|View full text |Cite
|
Sign up to set email alerts
|

Need for structure predicts leadership preference.

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Hence, people with a strong need for structure have a strong desire for workplace hierarchy (Friesen et al, 2014), perform better in clearly structured working tasks (Rietzschel, Slijkhuis, & van Yperen, 2014b), and are less innovative and creative (Rietzschel, Slijkhuis, & van Yperen, 2014a). Moreover, they prefer task-oriented leadership (Ehrhart & Klein, 2001) and react rather positively to close monitoring (Rietzschel et al, 2014b) and to prototypical leaders (Leicht, Crisp, & Randsley de Moura, 2013). On a more general level, people with high need for structure are more dogmatic and rigid, develop more routines, are more conscientious, are less open to experience, and have higher levels of neuroticism (Neuberg & Newsom, 1993;Machunsky & Meiser, 2006).…”
Section: Personal Need For Structurementioning
confidence: 99%
“…Hence, people with a strong need for structure have a strong desire for workplace hierarchy (Friesen et al, 2014), perform better in clearly structured working tasks (Rietzschel, Slijkhuis, & van Yperen, 2014b), and are less innovative and creative (Rietzschel, Slijkhuis, & van Yperen, 2014a). Moreover, they prefer task-oriented leadership (Ehrhart & Klein, 2001) and react rather positively to close monitoring (Rietzschel et al, 2014b) and to prototypical leaders (Leicht, Crisp, & Randsley de Moura, 2013). On a more general level, people with high need for structure are more dogmatic and rigid, develop more routines, are more conscientious, are less open to experience, and have higher levels of neuroticism (Neuberg & Newsom, 1993;Machunsky & Meiser, 2006).…”
Section: Personal Need For Structurementioning
confidence: 99%
“…On the one hand, researchers have shown that prototype-relevant leadership information may be processed centrally rather than heuristically van Knippenberg & Wilke, 1992). On the other hand, it has been argued that prototypebased leadership judgments may rely on prototypicality as a heuristic that circumvents more laborious systematic inductive information processing (e.g., Leicht, Crisp, & Randsley de Moura, 2013). Our findings show that uncertainty moderates how people process prototype-relevant information centrally versus heuristically.…”
Section: Discussionmentioning
confidence: 49%
“…Despite research showing that participants self-esteem can be negatively impacted by strong CONTESTING STEREOTYPES AND LEADERSHIP 26 female role models due to social comparison processes (Hoyt, Burnette, & Innella, 2012) this research shows that role models who inspire participants to challenge their stereotypes can affect social cognitive processes and decrease the tendency to associate good leadership with being group prototypical (Leicht et al, 2013;Hogg et al, 2012). Since leadership judgments are strongly affected by how closely individuals match the group prototype and or a leadership stereotype (Hogg & van Knippenberg, 2003) showing that exposing participants to examples of counter-stereotypical individuals can debias these judgments and can positively affect occupational choices and increase equality within the workplace.…”
Section: Theoretical Implicationsmentioning
confidence: 96%
“…Research has shown that individuals who prefer a stable and structured environment are more inclined to use group prototypicality for leadership judgments (Leicht et al, 2013). Additionally participants who are high in need for structure decrease their performance when being exposed to a counter-stereotypic target (Goscłowska & Crisp, 2013).…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation